Development of an Android-Based E-Module on Hypnoprenatal Material for Diploma III Midwifery Students - Sari Wahyuni; Nurul Komariah (Science Midwifery, 2026)
Mobile technology has become increasingly important in health professions education, yet midwifery learning in Indonesia still relies largely on printed modules and conventional lectures. Hypnoprenatal is a relaxation technique that has been reported in the literature as a complementary approach to reduce antenatal anxiety and fear of childbirth; however, digital instructional resources covering this topic for midwifery students remain limited. This study aimed to develop an Android-based hypnoprenatal e-module for Diploma III Midwifery students and to assess its feasibility as a learning medium, using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) as the research and development (R&D) framework. Methods: Feasibility was evaluated by two material experts, one media expert, one lecturer, and 20 fourth-semester students through validated five-point Likert-scale questionnaires. Responses were analyzed descriptively by calculating the percentage of agreement for each respondent group, which was then interpreted against a predetermined feasibility category scale (e.g., 81–100% = "Highly Feasible," 61–80% = "Feasible," and lower ranges indicating reduced feasibility). Results: After two rounds of expert validation and revision, the e-module obtained mean feasibility scores of 90.0% from the media expert and 96.3% from the material experts, both falling within the "Highly Feasible" category. Student feedback yielded 84.1% in the small-group trial and 90.1% in the large-group trial, while the lecturer's assessment reached 95.3%, all within the "Feasible" to "Highly Feasible" range. Conclusion: Based on these descriptive feasibility scores, the Android-based hypnoprenatal e-module is feasible for use as a self-directed learning medium for midwifery students. This study did not evaluate the e-module's effect on student learning outcomes or anxiety-related measures; further research employing experimental designs is needed to examine its effectiveness. . The findings nonetheless support the potential of this e-module as a starting point for integrating complementary-care content into competency-based midwifery education.